2018
DOI: 10.1097/aap.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Major Laparoscopic Intraperitoneal Surgery Performed With Combined Bilateral Subcostal Transversus Abdominal Plane Block and Celiac Plexus Block, Intravenous Sedation Without Tracheal Intubation

Abstract: To date, celiac plexus block has been used almost exclusively to relieve pancreatic cancer pain. This is the first report in which it is shown that major intra-abdominal surgery can be performed almost exclusively with regional anesthesia while avoiding adverse effects and problems associated with either general or neuraxial anesthesia. In addition, prolonged postoperative pain relief facilitated early recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2,3 CPB has also been employed more broadly for refractory hypertension and postoperative pain. [4][5][6] Studies have supported earlier use, such as at the time of attempted surgical resection in pancreatic cancer, regardless of preexistent pain, or before aggressive opioid dose escalation. [7][8][9] One study found improved CPB efficacy for pain duration of less than 2 months versus greater than 2 months.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 CPB has also been employed more broadly for refractory hypertension and postoperative pain. [4][5][6] Studies have supported earlier use, such as at the time of attempted surgical resection in pancreatic cancer, regardless of preexistent pain, or before aggressive opioid dose escalation. [7][8][9] One study found improved CPB efficacy for pain duration of less than 2 months versus greater than 2 months.…”
Section: Introductionmentioning
confidence: 99%
“…5 Blocks acting on the paravertebral sympathetic ganglions (ie, celiac plexus block) combined with a parietal block (ie, transverse abdominis plane [TAP] block) could be effective to inhibit somatic and visceral afferences of postoperative pain. 6 Local anesthetics administered intraperitoneally may also be effective. 7,8 Intravenous infusion of lidocaine decreases postoperative pain during and after abdominal surgery, improves patient rehabilitation, and decreases hospital length of stay.…”
mentioning
confidence: 99%